2017
DOI: 10.1177/0004563217694378
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of lipopolysaccharide-binding protein for sepsis in patients with suspected infection in the emergency department

Abstract: Background Biomarkers can facilitate the diagnosis of sepsis, enabling early management and improving outcomes. Lipopolysaccharide-binding protein (LBP) has been reported as a biomarker for the detection of infection, but its diagnostic value is controversial. In this study, we assessed the diagnostic accuracy of LBP for sepsis in the emergency department (ED) patients, comparing it with more established biomarkers of sepsis, including procalcitonin (PCT) and C-reactive protein (CRP). Methods LBP and other sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…LBP has an important role in the innate immune response, which binds to the lipid A moiety of LPS and promotes the release of cytokines. , In accordance with our result, García et al found that the diagnostic efficacy of LBP for sepsis was similar to that of CRP but lower than that of PCT in a study of 102 patients with suspected infections in the emergency department . Another study in rats revealed that blocking LBP by administration of a specific blockade peptide LBPK95A could significantly inhibit neutrophils infiltration .…”
Section: Discussionsupporting
confidence: 90%
“…LBP has an important role in the innate immune response, which binds to the lipid A moiety of LPS and promotes the release of cytokines. , In accordance with our result, García et al found that the diagnostic efficacy of LBP for sepsis was similar to that of CRP but lower than that of PCT in a study of 102 patients with suspected infections in the emergency department . Another study in rats revealed that blocking LBP by administration of a specific blockade peptide LBPK95A could significantly inhibit neutrophils infiltration .…”
Section: Discussionsupporting
confidence: 90%
“…Although PCT is considered superior to CRP in many studies [139,140], it is not a definitive test for diagnosing sepsis because PCT levels can also be increased in other conditions [141]. PCT, similar to CRP, may be more useful to rule out sepsis than to diagnose it [142][143][144], and the combination of these two biomarkers may improve their Table 2 Sepsis biomarkers, except for C-reactive protein (CRP) and procalcitonin (PCT), that have been evaluated for their prognostic value in clinical studies with more than 300 subjects (Continued) Lipopolysaccharidebinding protein ED patients with sepsis ED patients with infection No better than PCT [40] Non-critically ill patients with sepsis Non-critically ill patients with infection…”
Section: Discussionmentioning
confidence: 99%
“…During sepsis, previous studies suggested that levels of serum LBP elevated almost seven times higher than normal levels [ 24 ]. Therefore, LBP might be a promising tool for the early clinical diagnosis of sepsis and appropriated in differentiating sepsis and systemic inflammatory response syndrome (SIRS) [ 25 ]. It was reasonable to suppose the SNP affecting the expression or activities of LBP might also have influence on individual susceptibility for sepsis.…”
Section: Discussionmentioning
confidence: 99%